Адаптивна лазерна терапія - Borozenets, Danylo A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The article describes a method and device capable of improving the quality of laser-therapy procedures based on the recovery of the body after stress. The experiment was conducted on 13 healthy volunteers aged 20-55 years. The oxygen content of the blood, the dynamics of cellular immunity, and the transition of the gel to the sol were assessed during adverse environmental changes in the body. Tests were conducted in various modes from continuous supply of emission to pulsed with different frequencies and, as a result, coincided with the predicted results. For middle-aged people, who were the subjects of these experiments, there was a positive dynamics of recovery of the cellular immunity, pressure and oxygen content in the blood with regular procedures, although the latter has a temporary effect. The conclusions outline the capabilities of the system and suggest ways for improvement.